2020
DOI: 10.1007/s10008-020-04603-4
|View full text |Cite
|
Sign up to set email alerts
|

The immobilisation and reactivity of Fe(CN)63−/4− in an intrinsically microporous polyamine (PIM-EA-TB)

Abstract: Protonation of the molecularly rigid polymer of intrinsic microporosity PIM-EA-TB can be coupled to immobilisation of Fe(CN) 6 3−/4− (as well as immobilisation of Prussian blue) into 1-2 nm diameter channels. The resulting films provide redoxactive coatings on glassy carbon electrodes. Uptake, transport, and retention of Fe(CN) 6 3−/4− in the microporous polymer are strongly pH dependent requiring protonation of the PIM-EA-TB (pK A ≈ 4). Both Fe(CN) 6 4− and Fe(CN) 6 3− can be immobilised, but Fe(CN) 6 4− appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
(103 reference statements)
2
9
0
Order By: Relevance
“…The presence of the tertiary amine functional groups in the Tröger's base (TB) structural units of PIM-EA-TB provides sites for protonation, which occurs at approximately pH 4 in aqueous environments. 13 At solution pH values higher than 4, hydrogen bonding to these amine functional groups has been observed previously for Fe(CN) 6 3− and Fe(CN) 6 4− guest species 14 and for caffeic acid. 15 For many weakly acidic guest species, hydrogen bonding to the tertiary amine in the polymer backbone is likely to contribute to the strength of host–guest interactions and thereby likely to contribute to the rate of transport processes within PIM-EA-TB.…”
Section: Introductionsupporting
confidence: 54%
“…The presence of the tertiary amine functional groups in the Tröger's base (TB) structural units of PIM-EA-TB provides sites for protonation, which occurs at approximately pH 4 in aqueous environments. 13 At solution pH values higher than 4, hydrogen bonding to these amine functional groups has been observed previously for Fe(CN) 6 3− and Fe(CN) 6 4− guest species 14 and for caffeic acid. 15 For many weakly acidic guest species, hydrogen bonding to the tertiary amine in the polymer backbone is likely to contribute to the strength of host–guest interactions and thereby likely to contribute to the rate of transport processes within PIM-EA-TB.…”
Section: Introductionsupporting
confidence: 54%
“…It has recently been reported that guest species such as Fe(CN) 6 4À /3À can be accumulated and bound into PIM-EA-TB pores via hydrogen bonds. [19] It is shown here that other species such as caffeic acid readily accumulate. Furthermore, the hydrogen bonding host-guest interactions modify the transport processes during ion transport.…”
Section: Introductionmentioning
confidence: 64%
“…The permeation and transport of species in liquid-filled PIM microchannels can be employed in sensing and detection. PIM-EA-TB has tertiary amine functional groups on the polymer backbone and therefore allows interactions with hydrogen bond forming guests such as metal complexes [34] or herbal drugs such as catechin and quercetin [35]. Accumulation of these redox active species gave electrochemical oxidation signals proportional to the solution concentration with a Langmuir isotherm related response.…”
Section: Liquid Phase Analysismentioning
confidence: 99%